2003
DOI: 10.1021/np030146m
|View full text |Cite
|
Sign up to set email alerts
|

10-Methoxydihydrofuscin, Fuscinarin, and Fuscin, Novel Antagonists of the Human CCR5 Receptor from Oidiodendron griseum

Abstract: Two new compounds, 10-methoxydihydrofuscin (1) and fuscinarin (2), and one known compound, fuscin (3), have been isolated from the soil fungus Oidiodendron griseum. These compounds were found to compete effectively with macrophage inflammatory protein (MIP)-1 alpha for binding to human CCR5, an important anti HIV-1 target that interferes with HIV entry into cells. The structures of these compounds were elucidated by spectroscopic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 9 publications
1
54
0
1
Order By: Relevance
“…1 The isolation of fuscin (2) has also been reported by other researchers before. 2 The molecular structure of fuscin (2) was characterized by comparing its 1 H NMR and MS data with those in the literature, 2c,2d but the absolute stereochemistry and the specific rotation are still unknown. However, unlike fuscin, dihydrofuscin (4), a biosynthesis precursor of fuscin was first isolated from the fungus Potebniamyces gallicola as a natural product in 1983.…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…1 The isolation of fuscin (2) has also been reported by other researchers before. 2 The molecular structure of fuscin (2) was characterized by comparing its 1 H NMR and MS data with those in the literature, 2c,2d but the absolute stereochemistry and the specific rotation are still unknown. However, unlike fuscin, dihydrofuscin (4), a biosynthesis precursor of fuscin was first isolated from the fungus Potebniamyces gallicola as a natural product in 1983.…”
Section: Introductionsupporting
confidence: 64%
“…The novel pentaketide metabolites, fuscinarin (1) and two known pentaketide metabolites, fuscin (2) and 10-methoxydihydrofuscin (3), have been isolated recently from the fungus Oidiodendron griseum (a mitosporic fungus) ( Figure 1). 1 The isolation of fuscin (2) has also been reported by other researchers before.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, preliminary results showed that various concentrations of ␤-D-glucan did not induce eosinophil degranulation or superoxide production in vitro (data not shown). Finally, certain microorganisms, such as HIV and fungi, might directly interact with or produce a molecule(s) that binds to a cell's chemokine receptors (e.g., CCR5), which are coupled to certain G proteins (56,57). Additional studies are needed to identify the stimulatory component(s) in Alternaria extract and its receptor(s) on eosinophils.…”
Section: Discussionmentioning
confidence: 99%